Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai di PT Kereta Api Indonesia (Persero) UPT Balai Yasa Pulobrayan Medan - Hasibuan, Salsa Bila; Syafrizal, Syafrizal; Julkarnain, Julkarnain (Universitas Islam Islam Sumatera Utara, 2024)
The purpose ofthisstudyis to determine work motivation affects employee performance at PT Kereta ApiIndonesia (Persero) UPT. Balai Yasa Pulubrayan Medan. To find out the work environment and employee performance affect employees at PT Kereta Api Indonesia (Persero) UPT. Balai Yasa Pulubrayan Medan. The population in this study were 91 people, the sample was 91 people. The data collection method used is a questionnaire using validity and reliability measuring instruments to measure validity and reliability, then using data analysis methods using multiple regression analysis which is used to determine the effect between the independent variables and the dependent variable simultaneously and individually, using hypothesis testing in the form of t-test which is used to determine the extent to which the independent variables used individually are able to explain the dependent variable and the F-test is used to determine the extent to which the independent variables used simultaneously are able to explain the dependent variable. The coefficient of determination which measures how far the model's ability to explain the variation inthe dependent variable. Data analysis in this study used the help of IBM SPSS version 25. Personally (t-test) Work Motivation hasa positive and significant effect on employee performance at PT Kereta ApiIndonesia (Persero) UPT. Balai Yasa Pulubrayan Medan. The work environment also has a significant influence on employee performance at PT. Kereta Api Indonesia (Persero) UPT. Balai Yasa Pulubrayan Medan. The results of simultaneous significant testing (test -F) Work Motivation and Work Environment have a significant effect on employees at PT Kereta Api Indonesia (Persero) UPT. Balai Yasa Pulubrayan Medan